The Commercial-Civil Dichotomy of Business Organizations and Its Legal Significance under Ethiopian Law - Chanie, Gizachew Silesh (Bahir Dar University Journal of Law, 2022)
The classification of business organizations into commercial businessorganizations and civil business organizations (also known as non-commercial business organizations) is traditionally maintained inmost civil law countries. The Ethiopian legal system, which maintainsdistinct civil codes and commercial codes, also upholds theclassification of business organizations into commercial and civilbusiness organizations. With respect to this classification, a host ofissues remain blurred. What is the basis of the classification? Is thebasis of the classification clear cut? What are the legal consequencesof this classification? What legal frameworks do these categories ofbusiness organizations share and where do they differ? Do wenecessarily need to sustain this dichotomy anymore? Has anysubsequent legislation affected the earlier legal framework of thedistinction in the Commercial Code of Ethiopia? These issues andother related matters deserve critical consideration in the Ethiopiancontext. Through analysis of these issues, this article concludes thatthe civil-commercial dichotomy of business organizations is somewhatold-fashioned, at least in some respects, and under Ethiopian law, ithas put civil business organizations at a disadvantage.